MOTIF AKA CINO SAGAGANG PADA INTERIOR KELUARGA - Doli Indra Hanafi; Rahmad Washinton; Hendra Hendra (Institut Seni Indonesia Padangpanjang, 2022)
ABSTRACT Aka cino sagagang motive is one. On the motives applied to Rumah Gadang the motive of aka cino sagagang symbolize a determinate determination to achieves life,s goals this is line with the work to be made, namely the family is a place of basic education to foster personalities. The concept of creating this work departs from the farm of a motif that is stalized to adjust the field applied to the family interior. The theoretical basis used in the realization of this workis the theory used in the realization of this namely the theory of form, function, and aesthetics. The methods in the process of creating this work used the exsploration, design, and realization stages. The material us in the process of making this work is surian wood. The techniques used in making this work is the technique of carving and construction.The work created in three dimentions. This work has a practical and aesthetic function which is used as a disposable object in a family room which consists of a tv cabinet, bookcase, desk chair, display cabinet, and wall lamp. ABSTRAK Motif aka cino sagagang merupakan salah satu motif yang diterapkan pada rumah Gadang. Motif aka cino sagagang melambangkan suatu tekad yang gigih dalam mencapai tujuan hidup, hal ini sejalan dengan karya yang akan dibuat yaitu interior keluarga, di mana keluarga menjadi tempat pendidikan dasar untuk membina kepribadian.Konsep penciptaan karya ini berangkat dari bentuk motif yang distilisasikan menyesuaikan bidang yang diterapkan pada interior keluarga. Landasan teori yang digunakan dalam perwujudan karya ini yakni teori bentuk, fungsi, dan estetis. Metode dalam proses penciptaan karya ini menggunakan tahap eksplorasi, perancangan dan perwujudan. Bahan yang digunakan dalam pembuatan karya ini adalah kayu surian. Teknik yang digunakan dalam pembuatan karya ini adalah teknik ukir dan kontruksi.Karya yang diciptakan berbentuk tiga dimensi. Karya ini memiliki fungsi praktis dan estetis yang digunakan sebagai benda pakai dalam ruang keluarga yang terdiri dari kursi three seat, meja, rak buku, kabinet TV, lemari pajang, dan lampu dinding.